The Impact of Information Technology Investment on Firms Performance - Fatima Stores; Mohd Lizam Md Diah; Nor Hazana Abdullah; Zulida Abdul Kadir (LPPM of NAROTAMA UNIVERSITY, 2018)
Purpose: The aim of this study is to examine the relationship between information technology investment and firm’s performance among Malaysian PLCs. Design/methodology/approach: , The analysis employed panel data approach in which it relied on annual report of companies listed in Bursa Malaysia. This study covered a period between 2009 and 2012, therefore only companies listed within this stipulated period were included in the analysis. Findings: Results of the regression estimation of the dependent variables, based on random effect model shows a high significant on return of investment score. The control variables of firm size and industry did not have a statistically significant influence on the test results. However, IT investment is statistically not significant with return on asset, as there is no relationship between IT investment and ROA. Research limitations/implications: First, this study is using a limited sample data as an established large sample data set in relation to IT investment information in PLC’s is still unavailable. Secondly, this study is unable to investigate a time lag effect due to the limited information available in the annual reports. State your limitation here. Thirdly, the IT investments are divided into two asset classes, but there is several ways to characterize the ?rm’s investment allocations. Practical implications: This study substantiates the need for PLCs to increase their IT investment as the company grows. Information technology strategies need to be developed at par with company’s future direction. Originality/value: This study is one of the first empirically studies done in investigating the relationship between IT investment and firm financial performance in Malaysian PLC’s which is using the public listed companies’ secondary data. Paper type: Research paper